Screening of agroresidues for economical and sustainable Phytase Production by Bacteria - Suchita Bharambe,; Swati Peshwe,; Jayashree Bhuktar ,; Anjali Naik, (International Journal of Scientific Research in Science and Technology, 2024)
Phytase, a phytate hydrolysing enzyme has substantial application in food, feed and agriculture sector for improvising the availability of phosphorus and reduces the environmental pollution. The present study emphasizes on cost effective production of bacterial phytase. Total 25 agroresidues were screened for economic production of phytase using bacteria. A total of 30 bacterial isolates were obtained from poultry and goat shed soil and litter sample showing highest phytase activity. The efficient isolates SP-46 and SP-52 were screened for selection of efficient combination bacterial isolate and agroresidues for cost-effective production of phytase. The results showed that utilization of agroresidues not only serve as efficient substrate but also contribute to sustainable agro-waste valorisation and reduces need of expensive synthetic media for phytase production.
Keywords: Phytate; Bacterial Phytase; Agroresidues; Cost Effective Production